2020
DOI: 10.3390/ijms21082816
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Regulatory Role of m6A Epitranscriptome in Glioblastoma

Abstract: N6-methyladenosine (m6A) is one of the most widespread and abundant internal messenger RNA modifications found in eukaryotes. Emerging evidence suggests that this modification is strongly linked to the activation and inhibition of cancer pathways and is associated with prognostically significant tumour subtypes. The present review describes the dynamic nature of m6A regulator enzymes, as methyltransferases, demethylases and m6A binding proteins, and points out thevalue of the balance among these proteins in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 65 publications
2
26
0
Order By: Relevance
“…However, RNA m6A methylation in cancers is little studied. In GBM, m6A RNA demethylases have been clearly identified as oncogenic factors [ 11 ]. Cui et al showed that inhibition of the m6A RNA demethylase FTO with a specific inhibitor decreased GBMSC tumorigenicity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, RNA m6A methylation in cancers is little studied. In GBM, m6A RNA demethylases have been clearly identified as oncogenic factors [ 11 ]. Cui et al showed that inhibition of the m6A RNA demethylase FTO with a specific inhibitor decreased GBMSC tumorigenicity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, based on the evidence that m6A RNA methylation plays a significant role during development (Heck and Wilusz 2019;Li et al 2019;Vu et al 2019), our results suggest that environmental chemicals can influence developmental processes by altering an important layer of post-transcriptional regulation of mRNAs and noncoding RNAs. Furthermore, m6A RNA methylation has been shown to play a key role in normal physiology and metabolism, stress response and in various types of cancer (Engel et al, 2018;Galardi et al 2020;He et al 2019), suggesting additional toxicity mechanisms for environmental chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…They studied the levels of m 6 A RNA methylation in three GSC lines and showed that they were reduced uponin vitro differentiation. Moreover, they also found that METTL3 mRNA was clearly more abundant in GSCs compared to counterparts [ 82 , 83 ].…”
Section: Characteristics Of M6a Modification In Gliomasmentioning
confidence: 99%